Analysis of motor abilities in 16 to 18 years-old cross-country skiers across three consecutive training years - Sterzing, B.; Kock, H.; Schürer, A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Long-term training concepts in adolescent athletes are designed to emphasise training from general to specific motor abilities 2. Among physiological variables, e.g. aerobic, anaerobic capacity or maximal oxygen uptake, cross-country (XC) skiing performance is correlated with different motor skills 3. The purpose of the present study was to compare general motor abilities of german adolescent XC skiers in a 3-year period, where SARS-CoV-2 lockdown restrictions caused interruptions in regular training and annual fitness testing.